PEMINDAHTANGANAN BARANG MILIK NEGARA MELALUI HIBAH DALAM RANGKA MEWUJUDKAN PENGELOLAAN YANG TRANSPARAN DAN AKUNTABEL - Achmad Chodiq (CV. Denasya Smart Publisher, 2025)
The management and transfer of State-Owned Assets (BMN) through the grant mechanism is one of the government’s instruments to support national development and improve public welfare. However, in practice, the implementation of BMN grants encounters various challenges. From the administrative perspective, many government assets remain unrecorded in asset registers, damaged assets are not disposed of properly, causing imbalances in financial statements, and supporting documents for grants are often incomplete. From the technical perspective, obstacles arise due to the wide geographical distribution of assets, assets built on privately owned land, and limited regulations regarding grants to region-owned enterprises (BUMD). Other issues in the field include cases where recipients refuse grants after approval due to location or additional cost considerations, as well as applicants who submit multiple requests. These conditions indicate that the principles of good governance in state asset management have not been fully realized. Based on this background, the study aims to analyze and examine the policy of BMN transfer through grants within the perspective of good governance, while formulating more effective and efficient policy recommendations. This research employs a descriptive qualitative analysis by reviewing relevant regulations, including Law No. 17 of 2003 on State Finance, Government Regulation No. 28 of 2020 on the Management of State/Regional Assets, and Ministry of Finance Regulation No. 165/PMK.06/2021. The findings reveal that the implementation of BMN grants has not fully aligned with existing legal provisions, both in terms of policy and technical execution. This has led to suboptimal transparency, accountability, and effectiveness in the transfer of BMN. In conclusion, there is a need for strengthened policies and more comprehensive technical regulations to ensure that BMN grants are carried out transparently, accountably, and in accordance with the principles of good governance. Thus, this study contributes policy recommendations to enhance future BMN management.